Menyibak Relasi Kosmologi Dalam Budaya Blatan Balik Suku Ipir, Nuha, Dan Hebing Tanarawa-Maumere Dalam Terang Berfilsafat Budaya - Yosef Usman; Anastasia Any; Hermanus Ndode (Universitas Palangka Raya, 2024)
This research focuses on exploring the cosmological and humanization values contained in the Blatan Balikculture of the Ipir, Nuha and Hebing tribes gathered in one traditional house in Tanarawa, Waiblama, Maumere-Flores-East Nusa Tenggara. Blatan Balikculture is a rite that contains reconciling the cosmos with fellow creations or in the language of Tana Ai (blatan gahu rou), and the second is cooling valuable items stored in traditional houses such as gongs, bahar, ivory and other valuable objects in the traditional house (lepo). These two rites are an act of respect and reconciliation with creation. Therefore, exploring the comological and humanization wealth contained in the Blatan Balikculture is a form of respect for the nature of creation and also a process of humanization and the value of local wisdom. Respect for created nature and a process of humanization is the basis of life wisdom in the form of a framework of knowledge, a framework of belief both in integralistic family unity or unity in the wider community, and shows the noble values in the culture. So exploring the wealth of cosmology and humanization in the Blatan Balikculture is a form of respect for nature and reconciliation with fellow creatures and a life wisdom of the Tana Ai- Tanarawa, Waiblama, Maumere-Flores-East Nusa Tenggara community. This research uses qualitative research with data collection techniques through interviews and literature studies, collecting sources from journals, related books. This research found that the Blatan Balikculture of the Nuha Tanarawa tribe is a model of humanization and cosmology relations, between fellow humans, nature, other fellow creations and the giver of life. The values that flow from this culture are reconciliation and responsibility for nature, preservation of valuable objects in the Nuha tribe, and human harmony in relationships. The contribution of this research lies in the ultimate values and wisdom of the Tana Ai people in maintaining humanization relations between others and preserving nature.